Posted by **Amber** on Sunday, July 1, 2012 at 2:23am.

Given f(x) = radical x-2 and g(x) = x2 – x – 6. Find (f – g)(6).

A. -26

B. 26

C. -22

D. 22

E. 2

## Answer this Question

## Related Questions

- math,correction - Simplify by combining like terms. Problem #32 radical (63) - 2...
- math , help,algebra - i am up to this point in my problem but i don't know what ...
- Algebra - I'm adding 2(radical 50) + 12 (radical 8). I began by breaking the ...
- Trig - Given sin θ = −1/2 and sec θ > 0, find the exact value...
- algebra - 3 radical x - 4 radical y divided by 3 radical x - 2 radical y = ( i ...
- Algebra 1 - Am i on the right track? radical of 3 times radical of three= ...
- Algebra - Given f(x) = radical x-2 and g(x) = x2 – x – 6. Find (g o f)(6). A. -4...
- algebra - solve the equation or formula for the indicated variable R=ts^2+3 a)s=...
- maht,correction - Find the area of the rectangle shown in the figure. length = ...
- math,algebra,correction - Science and medicine. Find the time required for an ...